Perkembangan Fungsi Tari Ilau di Nagari Sumani Kecamatan X Koto Singkarak Kabupaten Solok - Yenti, Nanda Afri; Nerosti, Nerosti (Lembaga Yasin AlSys, 2025)
This study aims to describe and analyze the evolving function of Tari Ilau in Nagari Sumani, X Koto Singkarak District, Solok Regency. The primary focus is the transformation of Tari Ilau from its original sacred role performed exclusively during traditional wedding ceremonies into a more flexible form of performance featured in various social events, such as welcoming returning migrants, local election campaigns, and the 77th Indonesian Independence Day celebration in 2022. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through observation, interviews, literature review, and documentation. The findings indicate that changes in the function of Tari Ilau have influenced performance elements, including a reduction in the number of movement variations from ten to eight, simplification of floor patterns to a single circular formation, a shift in dancer demographics from those aged over 50 to adolescents aged 16–20, as well as adaptations in music and performance settings based on event contexts. The study concludes that Tari Ilau has undergone a significant transformation from a ritual function to aesthetic and social functions, reflecting the cultural dynamics of the Nagari Sumani community in responding to changing times.